Mixing between chemically variable primitive basalts creates and modifies crystal cargoes - David A. Neave (Nature Portfolio, 2021)
Chemically variable primitive basalts undergo mixing during ascent from the mantle. Here the authors show observations from magma–magma reaction experiments which demonstrate how isothermal mixing between chemically variable basalts creates and modifies crystal cargoes erupted in oceanic settings.